2012
DOI: 10.1073/pnas.1201475109
|View full text |Cite
|
Sign up to set email alerts
|

Footprints of positive selection associated with a mutation ( N1575Y ) in the voltage-gated sodium channel of Anopheles gambiae

Abstract: Insecticide resistance is an ideal model to study the emergence and spread of adaptative variants. In the African malaria mosquito, Anopheles gambiae, this is complemented by a strong public health rationale. In this insect, resistance to pyrethroid and DDT insecticides is strongly associated with the mutations L1014F and L1014S within the para voltage-gated sodium channel (VGSC). Across much of West Africa, 1014F frequency approaches fixation. Here, we document the emergence of a mutation, N1575Y, within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
245
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(267 citation statements)
references
References 40 publications
(50 reference statements)
12
245
1
Order By: Relevance
“…S4). The N1575Y SNP is associated with increased pyrethroid resistance and is found only on a resistant genetic background of L1014F (22). A synonymous SNP located 4,974 bp upstream of the L1014F was detected in association mapping for pyrethroid resistance (21).…”
Section: Resultsmentioning
confidence: 99%
“…S4). The N1575Y SNP is associated with increased pyrethroid resistance and is found only on a resistant genetic background of L1014F (22). A synonymous SNP located 4,974 bp upstream of the L1014F was detected in association mapping for pyrethroid resistance (21).…”
Section: Resultsmentioning
confidence: 99%
“…kdr R resistance is caused by mutations in the sodium channel: leucine to phenylalanine substitution, originally observed in West Africa [31], and leucine to serine mutation in East Africa [32]. Recently, a new mutation in the sodium channel associated with kdr-west mutation conferring additional resistance to DDT and permethrin [33] was reported [34]. Experimental studies conducted in Southern Benin and in South Africa respectively with lambdacyhalothrin [33] on bednets and with deltamethrin [33] through indoor residual house spraying [35] suggested that PYRs resistance may have contributed to the failure of vector control endeavours in these areas [21,[35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The N 1575 Y mutation is located in the intracellular cytoplasmic loop connecting domains III and IV (LIII/IV) (Fig. 1) F mutation (Jones et al, 2012). However, whether the N 1575 Y mutation confers pyrethroid resistance has not been functionally confirmed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new sodium channel mutation N 1575 Y was reported in the malaria mosquito, An. gambiae, in Africa (Jones et al, 2012). The N 1575 Y mutation is located in the intracellular cytoplasmic loop connecting domains III and IV (LIII/IV) (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation